2019
DOI: 10.1002/jcp.28440
|View full text |Cite
|
Sign up to set email alerts
|

ELP2 negatively regulates osteoblastic differentiation impaired by tumor necrosis factor α in MC3T3–E1 cells through STAT3 activation

Abstract: Tumor necrosis factor‐α (TNF‐α) is a pluripotent signaling molecule. The biological effect of TNF‐α includes slowing down osteogenic differentiation, which can lead to bone dysplasia in long‐term inflammatory microenvironments. Signal transducer and activator of transcription 3 (STAT3)‐interacting protein 1 (StIP1, also known as elongator complex protein 2, ELP2) play a role in inhibiting TNF‐α‐induced osteoblast differentiation. In the present study, we investigated whether and how ELP2 activation mediates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…NCAM deficiency inhibits osteoblast differentiation in both mouse preosteoblast cells and mouse adult stem cells, in which Wnt/bcatenin and Akt signaling pathways play important roles. MC3T3−E1, an osteoblast precursor cell line derived from mouse calvaria, has been widely used as a useful model for osteoblast differentiation research (21). Here, we explored the function of NCAM in osteoblast differentiation in MC3T3−E1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCAM deficiency inhibits osteoblast differentiation in both mouse preosteoblast cells and mouse adult stem cells, in which Wnt/bcatenin and Akt signaling pathways play important roles. MC3T3−E1, an osteoblast precursor cell line derived from mouse calvaria, has been widely used as a useful model for osteoblast differentiation research (21). Here, we explored the function of NCAM in osteoblast differentiation in MC3T3−E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…MC3T3−E1, an osteoblast precursor cell line derived from mouse calvaria, has been widely used as a useful model for osteoblast differentiation research ( 21 ). Here, we explored the function of NCAM in osteoblast differentiation in MC3T3−E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although temporary inflammation may promote bone healing, persistent and serious infection-associated inflammation could result in suboptimal and impaired bone regeneration [31, 32]. The newly formed bone was quantified by micro-CT, and results showed the volume of newly formed bone in the NBD + vancomycin group to be significantly higher than that in the Van or NBD group; the bone window eventually healed, indicating that NBD peptide could promote bone regeneration effectively only when infection was controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammatory cytokines play an important role in the promotion of bone resorption, via either the direct or indirect promotion of osteoclastogenesis, the effects of inflammatory cytokines on the osteoblastic differentiation of MSCs remain controversial, with regard to whether they are anabolic or catabolic factors for bone metabolism. Many studies have reported the reduced differentiation potential of MSCs treated with inflammatory cytokines, while there is increasing evidence indicating an important induction role played by inflammatory cytokine in osteogenic differentiation [9][10][11][12][13][14]32,33]. When examining the role played by TNF-α in the osteogenic differentiation of MSCs, Mountziaris et al [34] demonstrated that a lower dose of TNF-α (0.1-5.0 ng/mL) inhibited mineralization, whereas a higher dose (50 ng/mL) enhanced mineralization, in dexamethasone-pretreated rat MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-α is a major inflammatory cytokine that has been associated with bone loss in many inflammatory diseases. The influence of TNF-α on the osteoblastic differentiation of osteoprecursor cells has been reported to actively direct MSCs away from an osteoblastic fate [9][10][11]. However, the stimulatory effects of this cytokine, including the recruitment of MSCs and osteoblasts, have also been reported [12][13][14].…”
Section: Introductionmentioning
confidence: 99%